Comparison of correlation for Asia shariah indices using DCC-GARCH and rolling window correlation - Mohd Nazir, Muhammad Farhan; Mohamad, Nurul Najihah; Bahaludin, Hafizah (UniMAP Press, 2021)
This paper aims to compare the capability of correlation in capturing the volatility using rolling window correlation and Dynamic Conditional Correlation - Generalized Autoregressive Conditional Heteroscedasticity (DCC-GARCH) approach. This study will perform a DCC-GARCH to estimate the dynamic conditional correlation between the Asian Shariah indices. The Asian Shariah index comprises FTSE SGX Asia Shariah 100, FTSE Bursa Malaysia Emas Shariah Index, FTSE Greater China Shariah Index, and FTSE Stock Exchange of Thailand (SET) Shariah Index. The correlation estimation considers the FTSE SGX Asia Shariah 100 as a proxy. On the 11th of March 2020, The World Health Organization (WHO) has announced the Coronavirus 2019 (COVID-19) as pandemic. Therefore, the data used covers six months before and after 11th March 2020, from 11th September 2019 until 11th September 2020. The output of both effected correlations towards the Covid-19 will be evaluated based on their ability to capture the time-varying changes through graph plotting. The empirical findings show that the DCC-GARCH is better at capturing the highly changes volatility than the rolling window correlation.